2000
DOI: 10.1246/cl.2000.1104
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Polyamine Alkaloids by the Condensation of a Chiral β-Lactam with a Cyclic Imino Ether. (S)-Dihydroperiphylline and Its Derivatives

Abstract: The synthesis of 13-membered polyamine alkaloid, (S)-dihydroperiphylline, was achieved by the condensation of a chiral β-lactam, (S)-4-phenyl-2-azetidinone, with a cyclic imino ether of a 9-membered lactam, followed by reductive ring expansion. Both of these reactions proceeded with retention of configuration around the chiral center to give the optical pure 13-membered alkaloids.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2001
2001
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 17 publications
0
5
0
Order By: Relevance
“…Continuing our study in this direction, we paid attention to a number of publications [21][22][23][24][25]28,29] highlighting the synthesis of macrocyclic polyamine alkaloids, with the key step being reductive ring-expansion of bicyclic derivatives of 4-oxotetrahydropyrimidine 1 (Scheme 1, R=Ar). The reduction of bicycles 1 was carried out with sodium cyanoborohydride in acetic acid.…”
Section: Resultsmentioning
confidence: 99%
“…Continuing our study in this direction, we paid attention to a number of publications [21][22][23][24][25]28,29] highlighting the synthesis of macrocyclic polyamine alkaloids, with the key step being reductive ring-expansion of bicyclic derivatives of 4-oxotetrahydropyrimidine 1 (Scheme 1, R=Ar). The reduction of bicycles 1 was carried out with sodium cyanoborohydride in acetic acid.…”
Section: Resultsmentioning
confidence: 99%
“…[26c, 27,47] However, rac-14 b and rac-14 c could not be resolved by this method. Therefore, we applied enzymatic resolution protocols for these substrates.…”
Section: Resultsmentioning
confidence: 99%
“…The conjugate addition-cyclization reaction of piperidazine (5) to the optically active vinyl sulfoxide (S )-4 proceeded smoothly under basic conditions using potassium tert-butoxide in THF at room temperature to give the bicyclic compound 10, but the elimination of toluene-p-sulfenic acid ( p-TolSOH) from Scheme 1 10 occurred during its purification using column chromatography on silica gel, to give the unsaturated lactam 11 (Scheme 3).…”
Section: Conjugate Addition-cyclization Of Piperidazine (5) To Vinyl ...mentioning
confidence: 99%
“…Recently, the synthesis of a 13-membered lactam alkaloid, (S )-(ϩ)-dihydroperiphylline 2, starting from (S )-(Ϫ)-β-phenylβ-alanine, has been reported. 4, 5 Asymmetric synthesis of βamino acid derivatives using chiral vinyl sulfoxides has also proven to be useful methodology for the synthesis of chiral compounds. 6 Davis et al reported the diastereoselective synthesis of β-amino esters by addition of enolate ions to chiral sulfinimines.…”
Section: Introductionmentioning
confidence: 99%